Work-related disease symptoms and occupational injuries among coffee processing industry workers in Bench-Sheko and Kaffa Zones Southwest, Ethiopia: A mixed-method study - Mekonnen, Besufekad; Solomon, Nahom; Wondimu, Wondimagegn; Tesfaye, Melkamsew; Negash, Samuel (Frontiers in Public Health, 2022)
Background Occupational injuries have become one of the most critical rooting causes paying to infirmities and life-threatening conditions in developed and developing countries. Workers in the coffee industry face some occupational health and safety issues. However, there is limited evidence on this important public health issue. Hence, this research was conducted to assess work-related disease symptoms and occupational injuries among coffee processing workers in Southwest, Ethiopia. Methods A cross-sectional study supplemented with a qualitative method was done. A total of 721 workers were involved in the study for quantitative information. In addition, we performed a total of 22 in-depth and five key informant interviews for generating qualitative evidence. Quantitative data was collected by an interview-based questionnaire which is adapted from similar studies. We conducted descriptive, binary logistic, and multivariable regression analysis as necessary, to ascertain the factors affecting occupational injuries. We collected qualitative data guided by an interview guide, transcribed verbatim, and analyzed using ATLAS ti version-8 by applying a content analysis approach. Finally, quotes from participants that had exemplary ideas were triangulated along with quantitative findings. Result The overall prevalence rate of work-related symptoms and occupational injuries among coffee processing workers were 21.7 and 13.4% respectively. Age group 30–39 and 40–49 (Adjusted odds ratio (AOR) 1.95, 95% CI 1.37, 2.79, (AOR 3.28, 95% CI 1.89, 5.69, respectively, income level (AOR 0.24, 95% CI 0.16, 0.36, p = 0.000), experience (AOR 1.64, 95% CI 1.04, 2.60, p = 0.034), and smoking cigarette (AOR 5.59, 95% CI 2.78, 11.26, p = 0.000) were significantly associated with the work-related symptom. In addition, training related to the job (AOR 11.88, 95% CI1.34, 105.57, p = 0.026) was significantly associated with occupational injuries among coffee processing industry workers. Conclusion The prevalence of work-related symptoms and occupational injuries was high among coffee processing industry workers in southwest Ethiopia. Therefore, there is a need for regulations for both government and industry owners to advance the occupational conditions and ergonomic structure of coffee processing industries.